Technology strategies of the main actors and the strategies towards standards: the case of the diffusion of smart houses in Japan - Kumiko Miyazaki; Kentarou Nishida (International Telecommunications Society (ITS), 2015)
Various definitions of smart houses may exist but they have a common characteristic; through linking various modules components, electric appliances, technologies and sensors, smart houses aim to offer an innovative integrated solution to provide a level of smartness that has not existed in traditional houses. In smart houses, since various components, technologies and products have to be linked, standards become a critically important issue. At present, in Japan, Europe and the USA, 3 de jure standards related to smart houses exist, ECHONET-Lite, KNX and SEP. In this paper, an analysis is made of the technology and standardization strategies regarding ECHONETin Japan and a comparison is made with KNX. Eleven interviews with the main actors related to the ECHONET-Lite consortium and KNX were conducted. Three research questions were set; What are the technology strategy related concerns of the main actors related to ECHONET? What are the issues related to the diffusion of smart houses? What are the underlying strengths, weaknesses of ECHONET compared with KNX? The analyses showed that the strategies of the various actors towards the diffusion of smart houses were different, based on their different perspectives, visions and competences. A comparison between Japan with the European case highlighted the different standardization strategies and areas of focus. The main bottlenecks towards the diffusion of smart houses were identified. One of the major challenges to be overcome for the diffusion of smart houses is that a clear demand for smart houses has not been identified.
Keywords: 330; Smart house; Technology strategy; Standards; ECHONET; KNX